Effects of tranquilization therapy in elderly patients suffering from chronic non-communicable diseases: A meta-analysis - Li Jing; Li Jing; Cui Yulan; Li Honggeng; Hou Xiaoxuan; Zhao Fang; Zhao Qing; Zhao Junlan; Lin Pengchao (Acta Pharmaceutica)
The current meta-analysis searched the literature connected to different tranquilizers used to treat elderly people and assessed it in terms of dose, types of outcomes and adverse effects, to determine a safe and acceptable tranquilizer and its optimal dose. A systematic literature review was undertaken for randomized controlled trials, case-control, retrospective and prospective studies on the use of tranquilizers in elderly patients, using PubMed, Ebsco, SCOPUS and Web of Science. PICOS criteria were used to select studies, and pertinent event data was collected. This meta-analysis includes 16 randomized control trials spanning the years 2000 to 2022, using the data from 2224 patients. The trials that were included used various tranquilizers such as diazepam, alprazolam, temazepam and lorazepam, and indicated high treatment efficacy and low adverse effects. With a p-value of 0.853 for Egger’s test and 0.13 for Begg’s test, the current meta-analysis shows a minimal probability of publication bias. A recent meta-analysis supports the use of tranquilizers in older people to treat sleeplessness, epilepsy or anxiety, but only at modest doses, because large doses are harmful and produce numerous withdrawal symptoms.